Adapting multilingual speech representation model for a new, underresourced language through multilingual fine-tuning and continued pretraining. Issue 2 (March 2023) - Nowakowski, Karol; Ptaszynski, Michal; Murasaki, Kyoko; Nieuważny, Jagna
Abstract: In recent years, neural models learned through self-supervised pretraining on large scale multilingual text or speech data have exhibited promising results for underresourced languages, especially when a relatively large amount of data from related language(s) is available. While the technology has a potential for facilitating tasks carried out in language documentation projects, such as speech transcription, pretraining a multilingual model from scratch for every new language would be highly impractical. We investigate the possibility for adapting an existing multilingual wav2vec 2.0 model for a new language, focusing on actual fieldwork data from a critically endangered tongue: Ainu. Specifically, we (i) examine the feasibility of leveraging data from similar languages also in fine-tuning; (ii) verify whether the model's performance can be improved by further pretraining on target language data. Our results show that continued pretraining is the most effective method to adapt a wav2vec 2.0 model for a new language and leads to considerable reduction in error rates. Furthermore, we find that if a model pretrained on a related speech variety or an unrelated language with similar phonological characteristics is available, multilingual fine-tuning using additional data from that language can have positive impact on speech recognition performance when there is very little labeled data in the target language. Highlights: Downstream performance of a multilingual speech representation model on a new, underresourced language can be improved through multilingual fine-tuning and additional pretraining. Continued pretraining on target language data leads to substantially lower error rates in automatic speech transcription. Multilingual fine-tuning with additional data from a related or similar language helps when labeled target language data is scarce.